Identification and Molecular Characterization of a Novel Carlavirus Infecting Chrysanthemum morifolium in China - Jiapeng Li; Xiaoyin Wu; Hui Liu; Xiaomei Wang; Shaokui Yi; Xueting Zhong; Yaqin Wang; Zhanqi Wang (Viruses, 2023)
Chrysanthemum (Chrysanthemum morifolium) is an important ornamental and medicinal plant suffering from many viruses and viroids worldwide. In this study, a new carlavirus, tentatively named Chinese isolate of Carya illinoinensis carlavirus 1 (CiCV1-CN), was identified from chrysanthemum plants in Zhejiang Province, China. The genome sequence of CiCV1-CN was 8795 nucleotides (nt) in length, with a 68-nt 5′-untranslated region (UTR) and a 76-nt 3′-UTR, which contained six predicted open reading frames (ORFs) that encode six corresponding proteins of various sizes. Phylogenetic analyses based on full-length genome and coat protein sequences revealed that CiCV1-CN is in an evolutionary branch with chrysanthemum virus R (CVR) in the Carlavirus genus. Pairwise sequence identity analysis showed that, except for CiCV1, CiCV1-CN has the highest whole-genome sequence identity of 71.3% to CVR-X6. At the amino acid level, the highest identities of predicted proteins encoded by the ORF1, ORF2, ORF3, ORF4, ORF5, and ORF6 of CiCV1-CN were 77.1% in the CVR-X21 ORF1, 80.3% in the CVR-X13 ORF2, 74.8% in the CVR-X21 ORF3, 60.9% in the CVR-BJ ORF4, 90.2% in the CVR-X6 and CVR-TX ORF5s, and 79.4% in the CVR-X21 ORF6. Furthermore, we also found a transient expression of the cysteine-rich protein (CRP) encoded by the ORF6 of CiCV1-CN in Nicotiana benthamiana plants using a potato virus X-based vector, which can result in a downward leaf curl and hypersensitive cell death over the time course. These results demonstrated that CiCV1-CN is a pathogenic virus and C. morifolium is a natural host of CiCV1.